AN OVERVIEW OF BRYOPHYTES DIVISION - Nurmaini Ginting; Hanifah Mutia Z.N Amrul; Ferdinand Susilo (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Bryophyte is a non-vascular plant, consisting of three classes: mosses, hornworts, and liverworts. The body forms have a thallus, and some have a leaf-like organ. The class division of the Bryophyte division is base on anatomical and morphological traits, such as meristem tissues, stomata, and vascular tissues. M Bryophyte has no vascular tissue, but it has a capillary that has functions like xylem and commonly refers to as hydroid. Mosses and hornworts have stomata on the sporophyte part, while in the liverworts, stomata are not found. Hornworts have a basal meristem that has an unpredictable cleavage. Meristem on the mosses only divides up the formation of sporangial. In the liverworts, the apical meristem does not see. Members of the hornworts consider the most advanced because the meristematic phase is more prolonged, so that it is closer to the characteristics of Tracheophyta group.